PENGARUH FINANCIAL DISTRESS DAN LEVERAGE TERHADAP MANAJEMEN LABA (Studi Kasus Pada Perusahaan Sub sektor Farmasi Periode 2017-2021) - Tania Eka Putri Tania; Syamsul Huda (FKIP Unswagati, 2023)
This study intends to investigate how financial distress and leverage affect managing profitability. The populationof this study includes all pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the2017-2021 period, the sample was determined by purposive sampling, namely 8 companies. The data collectiontechnique uses documentation techniques, namely collecting financial reports for the pharmaceutical sub-sectorin the 2017-2021 period. This research method uses quantitative methods with descriptive and verification dataanalysis techniques and hypothesis testing using multiple linear regression analysis models. The results show thatthe coefficient of determination (R Square) indicates that financial distress and leverage impact earningsmanagement by 20.2%, whereas other factors not included in this study influence the remaining factors. Partialhypothesis testing shows that financial distress has no effect on earnings management while leverage has asignificant effect on earnings management. Simultaneously financial distress and leverage have a significant effecton earnings management in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the2017-2021 period.